The answer is 32 all you have to do to get you answer is add 3 and 2 which gives you 5 and you add it up until you get to 67 and you have to see how many times you add it up to get the answer which is 3 or a shorter way is 31 times 2 plus 5 and it gives you 67
Answer:
Step-by-step explanation:
The 9th term is the next-to-last term, where the left term of the binomial is raised to the first power, the right term of the binomial is raised to the 8th power (9-1=8), and the multiplier is 9C8 = 9!/(8!·1!) = 9. This product is ...
9·(3x)^1·(-2y)^8 = 6912xy^8
Answer:
8
Step-by-step explanation:
(36.0-(4.0+24.0))
Answer:
53
Step-by-step explanation:
65x- 12 = 43x + 10
65x - 43x = 10 + 12
22x = 22
x = 22/22
<u>x = 1 </u>
(65x- 12) =
65 * 1 - 12 =<u> 53</u>
43x + 10
43 * 1 -12 = <u>53</u>
I think that would be 1 by 3 feet
3 is my answer